English Self-Assessment Based on Pluralism in Preventing Radicalism - Santi Andriyani; Hayu Diah Yulistianti; Nusrotus Saidah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
The practice of radicalism in Indonesia has increased among all age groups, including young generation. They were mostly affected by radicalism and extremism. The aim of this study was to find out the implementation of English Self-Assessment Based on Pluralism in Preventing Youth Radicalism. This study used a descriptive analysis method. The instrument of this study was the students’ self-assessment worksheet focused on pluralism materials. The result showed that the implementation of English self-assessment through the values ​​of pluralism can improve the students’ understanding by using the technique of reading comprehension. And the religious understanding of the students was good criteria Keywords: English Self-Assessment, Preventing Radicalism, Self-Assessment